2017
DOI: 10.1038/ni.3694
|View full text |Cite
|
Sign up to set email alerts
|

Essential role for the transcription factor Bhlhe41 in regulating the development, self-renewal and BCR repertoire of B-1a cells

Abstract: Innate-like B-1a cells provide a first line of defense against pathogens, yet little is known about their transcriptional control. Here we identified an essential role of the transcription factor Bhlhe41, with a lesser contribution of Bhlhe40, in controlling late stages of B-1a cell differentiation. Bhlhe41–/–Bhlhe40–/– B-1a cells were severely reduced as compared to their wild-type counterparts. Mutant B-1a cells exhibited an abnormal cell-surface phenotype and altered B-cell receptor (BCR) repertoire exempli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(159 citation statements)
references
References 67 publications
12
147
0
Order By: Relevance
“…In comparison to the other macrophage subsets in the kidney, CM2 upregulated several genes associated with tissue remodeling including MMP2, ADAMTS10 and HTRA1. The functions of several other genes preferentially expressed by CM2 are not well defined in macrophages; however, they did express BHLHE41, a gene that is also expressed in microglia and lung resident macrophage populations 17 , consistent with CM2 representing resident cells. Compared to CM2 cells from LD controls, lupus CM2 cells expressed higher levels of interferon stimulated genes, as well as anti-inflammatory genes (GRN, TMSB4X, CREB5) and inhibitors of TLR signaling (GIT2, TNFAIP8L2), and lower levels of proinflammatory genes (ALOX15B, WNT5A) (Supplementary Table 5) 17 .…”
Section: Classification and Annotation Of Myeloid Cell Clusters Reveamentioning
confidence: 74%
“…In comparison to the other macrophage subsets in the kidney, CM2 upregulated several genes associated with tissue remodeling including MMP2, ADAMTS10 and HTRA1. The functions of several other genes preferentially expressed by CM2 are not well defined in macrophages; however, they did express BHLHE41, a gene that is also expressed in microglia and lung resident macrophage populations 17 , consistent with CM2 representing resident cells. Compared to CM2 cells from LD controls, lupus CM2 cells expressed higher levels of interferon stimulated genes, as well as anti-inflammatory genes (GRN, TMSB4X, CREB5) and inhibitors of TLR signaling (GIT2, TNFAIP8L2), and lower levels of proinflammatory genes (ALOX15B, WNT5A) (Supplementary Table 5) 17 .…”
Section: Classification and Annotation Of Myeloid Cell Clusters Reveamentioning
confidence: 74%
“…Peak calling with a stringent P value of < 10 −10 identified 12,740 Bhlhe40‐binding regions, and assignment of the peaks to the nearest gene within a 50‐kb window defined 6,517 Bhlhe40 target genes (data not shown). De novo motif discovery identified the CACGTG version of the E‐box (Fig C) that we and others previously described as the Bhlhe40/Bhlhe41 binding motif (Jolma et al , ; Kreslavsky et al , ). Almost half of the Bhlhe40‐binding sites were observed within gene bodies, whereas only 28% of the binding sites were present in intergenic regions (Fig D).…”
Section: Resultsmentioning
confidence: 99%
“…We first identified the transcription factors Bhlhe41 and Bhlhe40 as regulators of the development and self‐renewal of fetal‐derived innate‐like B‐1a cells (Kreslavsky et al , ). The results reported here indicate that these factors are important regulators of another self‐renewing tissue‐resident leukocyte population—AMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, the role of the transcription factors Bhlhe40 and Bhlhe41, in controlling late stages of B‐1a cell differentiation was established. B‐1a cells numbers were found highly reduced in Bhlhe40 –/– Bhlhe41 –/– mice when compared to their wild‐type counterparts . The experiments suggested that Bhlhe41 can repress the expression of cell cycle and BCR signaling regulators at the same time that allows pro‐survival cytokine signaling in these cells, thus promoting their self‐renewal …”
Section: B‐1 Lymphocytesmentioning
confidence: 96%